Modeling age and growth of the bigeye thresher (Alopias superciliosus) in the Atlantic Ocean - Fernandez-Carvalho, Joana (2015)
The bigeye thresher (Alopias superciliosus) is a pelagic shark captured as bycatch in pelagic longline fisheries. Important information on its biology is still missing, especially from the Atlantic Ocean. In all, 546 vertebrae collected by fishery observers between 2007 and 2009 were used to estimate age and growth parameters for this species in the Atlantic Ocean. The size composition was 102–265 cm fork length (FL) for females and 94–260 cm FL for males. The estimated ages ranged from 0 to 25 years for both sexes. From the 5 growth models used, the 3-parameter von Bertalanffy growth model, reparameterized to estimate length at birth (L0), produced the best results. The estimated parameters were asymptotic maximum length (Linf)=284 cm FL, growth coefficient (k)=0.06/year, and L0=109 cm FL for females and Linf=246 cm FL, k=0.09/year, and L0=108 cm FL for males. Although differences between hemispheres indicate slower growth rates in the South Atlantic Ocean, these differences may also have been caused by the lower sample size and larger specimen sizes for the Southern Hemisphere. The estimated growth coefficients are among the lowest found for the Alopiidae, highlighting the bigeye thresher’s slow growth and consequent low resilience to fishing pressure.